2015
DOI: 10.2147/oajsm.s82295
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between performance test and body composition/physical strength characteristic in sprint canoe and kayak paddlers

Abstract: ObjectiveCanoe sprint is divided into canoe and kayak. The difference between the two competitions is in physical performance. The aim of the present study was to compare and investigate the relationship between physical characteristics and fitness between the two canoe sprint competitors.MethodsSubjects were 11 canoe paddlers (C) and 12 kayak paddlers (K). They underwent anthropometric characteristics, body composition and fitness tests, and 120 s all-out tests using a canoe and kayak ergometer. The unpaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…One way to compensate for the missed on-water training is to emphasize the improvement of physical fitness through event-specific exercises. There is evidence that measures of muscular fitness [i.e., muscle strength (0.5 ≤ r ≤ 0.9), muscle power (0.6 ≤ r ≤ 0.7), muscular endurance (0.5 ≤ r ≤ 0.9)] maximum oxygen uptake (0.6 ≤ r ≤ 0.9), and skeletal muscle mass (0.4 ≤ r ≤ 0.9) are associated with kayak/canoe performance in kayakers competing at regional to international level ( Fry and Morton, 1991 ; Van Someren and Howatson, 2008 ; Forbes et al, 2009 ; Hamano et al, 2015 ). As a common element across regression models (0.66 ≤ R 2 ≤ 0.87), work generated during ergometer or bench pull exercises for 30–120 s on land might be an accurate predictor of on-water performance (200–2,000 m) in kayakers and canoeists from regional to international competitive level ( Van Someren and Howatson, 2008 ; Gäbler et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to compensate for the missed on-water training is to emphasize the improvement of physical fitness through event-specific exercises. There is evidence that measures of muscular fitness [i.e., muscle strength (0.5 ≤ r ≤ 0.9), muscle power (0.6 ≤ r ≤ 0.7), muscular endurance (0.5 ≤ r ≤ 0.9)] maximum oxygen uptake (0.6 ≤ r ≤ 0.9), and skeletal muscle mass (0.4 ≤ r ≤ 0.9) are associated with kayak/canoe performance in kayakers competing at regional to international level ( Fry and Morton, 1991 ; Van Someren and Howatson, 2008 ; Forbes et al, 2009 ; Hamano et al, 2015 ). As a common element across regression models (0.66 ≤ R 2 ≤ 0.87), work generated during ergometer or bench pull exercises for 30–120 s on land might be an accurate predictor of on-water performance (200–2,000 m) in kayakers and canoeists from regional to international competitive level ( Van Someren and Howatson, 2008 ; Gäbler et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Larger effect sizes were observed at training intensities above 85% 1-RM ( 2.5) with six to eight repetitions ( 2.4) in young athletes ( Lesinski et al, 2016 ). Moderate to high intensity (>70% 1-RM), low volume (MILV) strength training could be well suited for young kayakers and canoeists, because it increases muscle strength and hypertrophy, which are both associated with canoe and kayak performance ( Fry and Morton, 1991 ; Van Someren and Howatson, 2008 ; Forbes et al, 2009 ; Hamano et al, 2015 ). However, anecdotal evidence indicates that German top-level kayak/canoe coaches prefer low intensity, high volume (LIHV) strength training.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated contractions of the forearms are required for many daily physical activities and forearm strength and endurance are known to be performance-limiting factors in sports, such as rock climbing and canoeing [11,18]. It has been demonstrated that lower ambient temperature (10 °C) prolongs forearm flexor endurance during intermittent contractions [19] and that the optimal muscle temperature for sustained isometric contractions varies between 25 and 30 °C [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, specific movement patterns vary to a certain extent between the two disciplines based on the constraints of the task (e.g. rules, boat type) while physical/physiological and anthropometric characteristics do to a lesser extent 17 . Furthermore, young paddlers have a distinct physical and anthropometric profile that maybe advantageous for prospective paddling athletes to possess.…”
Section: Introductionmentioning
confidence: 99%